2021
DOI: 10.31616/asj.2020.0173
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of Bone Marrow Edema in Adolescent Athletes with Lumbar Spondylolysis Using Contrast Ratio on Magnetic Resonance Imaging

Abstract: Study Design: Prospective cohort study.Purpose: To quantitatively evaluate bone marrow edema (BME) in the pedicle on magnetic resonance imaging (MRI) for adolescent athlete patients with spondylolysis.Overview of Literature: Spondylolysis, a stress fracture of the pars interarticularis, is a common occurrence in adolescent athletes with low back pain. T2-weighed fat-saturated MRI is reportedly useful for the detection of BME in the pedicle in the early stage of spondylolysis; however, to our knowledge, the qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…[33,34] In a previous study, MR images of acute and subacute SCI showed T2 high-intensity lesions with unclear boundaries spread in the sagittal direction. [27] In the present study, similar features to those of T2 high-intensity lesions in SCI were observed. In contrast, intramedullary T2 high-intensity lesions with sharp boundaries are often confined to the interbody region in CCM.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…[33,34] In a previous study, MR images of acute and subacute SCI showed T2 high-intensity lesions with unclear boundaries spread in the sagittal direction. [27] In the present study, similar features to those of T2 high-intensity lesions in SCI were observed. In contrast, intramedullary T2 high-intensity lesions with sharp boundaries are often confined to the interbody region in CCM.…”
Section: Discussionsupporting
confidence: 86%
“…[23,24] Contrast ratio (CR) was used as the formula to calculate the above ratio. [25][26][27] The SI values of the intramedullary high-intensity lesion (H) and the spinal cord at the level of the first thoracic vertebra (C) were used to calculate the CR using the following formula:…”
Section: Mri Assessmentsmentioning
confidence: 99%
“…Although some studies have reported on the use of CRs on MRI in the pulmonary and liver fields [ 7 ], few trials have reported on CR use in spine research [ 19 , 20 ]. In the present cross-sectional study, the CR value of BME adjacent to the vertebral endplate was significantly higher than that in the normal bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…Low back pain in athletes may also arise from lumbar spondylolysis or a stress fracture of the pars interarticularis in the lumbar spine 3,4 . Lumbar stress fracture is caused by repetitive extension and rotation force of the lumbar spine, and magnetic resonance imaging (MRI) is a useful diagnostic tool for detecting stress fractures in their early stage 5–7 …”
mentioning
confidence: 99%
“…3,4 Lumbar stress fracture is caused by repetitive extension and rotation force of the lumbar spine, and magnetic resonance imaging (MRI) is a useful diagnostic tool for detecting stress fractures in their early stage. [5][6][7] Among stress fractures in the lumbosacral region, sacral stress fractures are considered an unusual cause of low back pain in athletes. 8,9 As adolescents have developing bones with high elasticity, sacral stress fractures are likely to occur in athletes because they are caused by excessive repetitive movements of the trunk.…”
mentioning
confidence: 99%